Strategic Leadership for Strengthening Teachers' Islamic Character and Building School Resilience in an Islamic Elementary School - Akhmad Fauzi Hamzah; Rosena Maulida (Edudeena : Journal of Islamic Religious Education, 2026)
School leadership plays an important role in strengthening teachers' professional identity and enhancing school resilience, particularly in Islamic educational institutions that integrate academic excellence with religious values. This study explores how Islamic-values-based principal leadership contributes to strengthening teachers' Islamic character and supporting school resilience at SD IT Al-Busyro, an Islamic integrated elementary school in Indonesia. A qualitative case study design was employed using semi-structured interviews with the principal, teachers, and school administrators, complemented by participant observation and document analysis. Data were analyzed through thematic analysis to identify recurring leadership practices and their influence on teachers and the school environment. The findings indicate four interconnected leadership strategies: transformational leadership grounded in prophetic values (amanah, siddiq, tabligh, and fathonah), exemplary role modeling (uswah), integrated professional and spiritual development, and participatory decision-making (musyawarah). These strategies foster teachers' commitment to professional responsibilities while strengthening Islamic values in daily educational practices. The study also finds that consistent integration of religious values into leadership practices contributes to a collaborative school culture and enhances the school's capacity to respond to organizational and external challenges. This study extends the discussion of educational leadership by demonstrating how Islamic values can be integrated into leadership practices to support teacher character development and school resilience. The findings may serve as a practical reference for leadership development in Islamic schools operating in the context of contemporary educational change.